Suboptimal health status of nurses in Wuhan, China during the COVID-19 outbreak - Liu,Huan (2021)
SUMMARY OBJECTIVE: This study analyzes the suboptimal health status (SHS) and influencing factors of nurses in Wuhan Hospital, China during the coronavirus disease 2019 (COVID-19) outbreak. METHODS: This study was conducted through an online survey, from March 1–7, 2020, in Wuhan, China. The data collection tools, such as Suboptimal Health Status Questionnaires, Generalized Anxiety Disorder, and Chinese version of the Perceived Stress Scale, were used. RESULTS: The average value of suboptimal health status was 28.44 (standard deviation=15.15). The overall prevalence of SHS was 35.1%. Suboptimal health status of the nurses was significantly different based on their gender, age, whether they directly care for COVID-19 patients, anxiety level, and stress perception expect education. Multivariate analysis found that average sleep times per day, female, age, directly participate in the rescue of COVID-19, self-infection, and anxiety were the influencing factors of suboptimal health status. CONCLUSIONS: First-line nurses have poor suboptimal health status in Wuhan.